Lewis Acid Catalyzed SN2-Type Domino Ring-Opening Cyclization (DROC) of Aziridines with Alkynes: A Synthetic Route to 2,3-Dihydropyrroles - Shukla, Dipti; Kashyap, Suraj; Singh, Bharat; Sharma, Amit Kumar; Bhattacharyya, Aditya; Rahman, Noimur; Ghorai, Manas K. (Synthesis, 2024)
A simple strategy for the synthesis of a variety of dihydropyrroles in good to excellent yields via a Lewis acid catalyzed, quaternary ammonium salt mediated SN2-type ring opening followed by cyclization of activated aziridines with alkynes in a domino fashion is described. The formation and the observed stereoselectivities of the products via an SN2-/double SN2-type ring-opening pathway are rationalized by mechanistic studies.
Keywords: aziridines; alkynes; dihydropyrroles; SN2-type ring opening; DROC